Multi-damage localization on large complex structures through an extended delay-and-sum based method. (January 2016) - Shan, Shengbo; Qiu, Jinhao; Zhang, Chao; Ji, Hongli; Cheng, Li
In this work, the technique of the delay-and-sum method has been extended to the localization of multi-damage on large complex structures. Through a case study by locating multiple damages on a composite aircraft panel, the exact extensions of the method are clearly presented. A multi-damage detection method is first designed on the basis of the propagating characteristics of Lamb waves as the preprocessing of damage localization. In light of the high signal complexity induced by the structural characteristics, an adaptive valid data extraction strategy is presented, improving the adaptability of the delay-and-sum method for complicated structures in terms of the damage localization accuracy. Since the localization accuracy of the delay-and-sum method can be significantly influenced by the uncertainty of preset velocity, it is further assessed by a quantitative localization accuracy evaluation method, revealing some fundamental features of the method in a comprehensive way. In addition, a boundary processing approach is designed to extend the delay-and-sum method for the multi-damage case. Experimental results in different damage situations verify that multi-damage can be located accurately by the proposed extended method.